PP452 Impact Of Patient Access Schemes On Health Technology Assessment Agency Guidance For Rare Diseases In England and Scotland. (December 2021) - Mark, Karen; Manchanda, Prachi; Rubinstein, Judith; Inumerable, Riza Veronica
Abstract : Introduction: Patient access schemes (PAS) are agreements that may enable patients to access drugs or other treatments that may not be cost effective under normal circumstances. The aim of this study was to determine whether the use of PAS by the National Institute for Health and Care Excellence (NICE) and Scottish Medicines Consortium (SMC) for recommended drugs can lead to greater access to medications for rare diseases. Methods: Reimbursement data for rare diseases between 2004 and 2021 from health technology assessment (HTA) agencies, namely the SMC (Scotland) and NICE (England), were included. The reviews with positive HTA decisions were considered, while those with negative decisions were excluded. Several observations were made from these data and reported. Results: Among the total positive reviews (n = 81), 43 included PAS. The inclusion of PAS in manufacturer submissions was more frequent for NICE than for the SMC (79% and 40% percent, respectively). Most of the drugs with PAS were included in the HTA guidance from both agencies. The positive NICE reviews contingent on PAS consisted of 20 drugs. For the same set of drugs, the SMC recommended 14 with PAS and one without PAS; five drugs were not assessed. Adalimumab was recommended by NICE with a PAS (base-case incremental cost-effectiveness ratio of GBP12, 336 [EUR14, 256]; GBP13, 676 [EUR15, 804]) and by the SMC without a PAS (base-case incremental cost-effectiveness ratio of GBP22, 519 [EUR26, 023]). Hence, without a PAS, the drug was costlier per quality-adjusted life-year for the National Health Service (NHS) Scotland. Conclusions: PAS submissions for rare diseases are more frequent for NICE than for the SMC. With the PAS discounts, the overall cost of the drugs is reduced, resulting in cost effectiveness. The SMC approved some drugs for which NICE required a PAS to improve the economic argument. Hence, the use of PAS for these drugs could lead to potential cost-savings to the NHS Scotland.